Ceftolozane-tazobactam and ceftazidime-avibactam activity against β-lactam-resistant Pseudomonas aeruginosa and extended-spectrum β-lactamase-producing Enterobacterales clinical isolates from U.S. medical centres. (September 2020) - Hirsch, Elizabeth B.; Brigman, Hunter V.; Zucchi, Paola C.; Chen, Alice; Anderson, Jadyn C.; Eliopoulos, George M.; Cheung, Nicole; Gilbertsen, Adam; Hunter, Ryan C.; Emery, Christopher L.; Bias, Tiffany E.
Highlights: We compared C/T and CZA activity against ESBL-producing Enterobacterales and β-lactam-resistant Pseudomonas aeruginosa . β-lactamase genes were identified in Enterobacterales with increased C/T or CZA MIC values. More than 90% of Enterobacterales isolates demonstrated susceptibility to both C/T and CZA. Both agents were active against >80% of β-lactam-resistant P. aeruginosa isolates. Abstract: Background: Despite availability of ceftolozane-tazobactam (C/T) and ceftazidime-avibactam (CZA) for several years, the individual spectrum of activity of each agent may not be widely known. We compared the activity of C/T and CZA against convenience samples of 119 extended-spectrum β-lactamase (ESBL)-producing Enterobacterales and 60 β-lactam-resistant Pseudomonas aeruginosa clinical isolates collected from three U.S. institutions. Methods: Minimal inhibitory concentrations (MICs) for C/T and CZA were determined by broth microdilution. Molecular identification of nine β-lactamase gene targets was conducted for Enterobacterales and P. aeruginosa isolates with increased MICs to C/T or CZA. Results: More than 90% of Enterobacterales isolates demonstrated susceptibility to both C/T and CZA, in contrast to the other traditional β-lactam agents tested, which were much less active. The MIC50/90 values were nearly equivalent between agents. The most common β-lactamase genes identified in Enterobacterales isolates with MIC values ≥2 mg/L were the CTX-M-1 group (85%) and CMY-2-like (23%) β-lactamases. Both agents were active against >80% of β-lactam-resistant P. aeruginosa isolates tested, most of which had oprD mutations identified. One P. aeruginosa isolate was positive for a Klebsiella pneumoniae carbapenemase-type gene but remained meropenem-susceptible. The MIC50 values were four-fold lower in favour of C/T (1 mg/L vs. 4 mg/L) against P. aeruginosa . Conclusions: Our data suggest that either agent may be a reasonable choice for centres with a high proportion of ESBL producers; however, C/T may have improved activity against P. aeruginosa and may be preferred in institutions with a higher frequency of resistant pseudomonal isolates.